Educational Beliefs of Prospective Physical Education and Sports Teachers - Yunus Emre Karakaya; Fatih Mehmet Ugurlu; İsmail Polatcan and Metin Yilmaz and Tamer Karademir (Journal of Educational Issues, 2024)
This study was conducted to reveal the educational beliefs of prospective physical education and sports teachers, who receive education at the higher education level in Turkey, according to dependent and independent variables. Within this scope, the “Educational Belief Scale” was used to collect the data from 359 prospective teachers. The data collected from the sample were first analyzed by SPSS 22.0 package software. In the correlation analysis, it was observed that the “Educational Beliefs Scale” and the progressivism subscale were correlated very strongly and positively, which was the strongest correlation in the analysis (r = 0.918; p < 0.05). In the regression analysis, four different model structures were created, where it was determined that the subscale with the highest prediction power for the “Educational Beliefs Scale” was the progressivism subscale that predicted 84% of the variance of the “Educational Beliefs Scale” (R2 = 0.840). In conclusion, it was discovered that the prospective teachers did not internalize the fundamentalism, which is included in the traditional educational philosophy. Significant responsibilities fall on the shoulders of academics and decision-makers to enable prospective teachers to save the valuable sections of basic information and values of the past and transfer them to new generations while approaching teaching with a perspective that promotes the potential of new generations in building a better civilization upon the achievements of past generations.